AQUACULTURE IN VAN PROVINCE - Mehmet BOZKOYUN (Fırat University, 2021)
In this study, the current situation and capacity of aquaculture in Van province is discussed. Van region corresponds to 2.7 percent of Turkey's land area with 20,921 square kilometers. Located in the Eastern Anatolia Region geographically, Van province has the status of Metropolitan and has 3 districts together with 13 districts in total. The average elevation of Van city center, which is located within the borders of Lake Van closed basin, is 1690 meters. Ağrı (Hamur, Taşlıçay, Diyadin and Doğubeyazıt districts) to the north of Van, Siirt (Pervari district), Şırnak (Beytüşşebap district), Hakkari provincial center and Yüksekova district in the south, Patnos district of Ağrı, Bitlis (Adilcevaz Tatvan and Hizan districts) and Lake Van in the west and Iran to the east. The purpose of this study is to determine the current situation and capacity of aquaculture in Van province, and to develop the problems of the sector and suggestions for solutions to these problems. While the culture fish production in Van province was 300 tons in 2000, it increased to 917 tons in 2010. The biggest leap in production over all years was in 2012. As a matter of fact, an increase of 757 tons (40.9%) has been achieved in production compared to the previous year. Another feature of this year is the production exceeded 2000 tons for the first time. Although this increase trend was interrupted in 2014, the production increased slightly in the next two years. Production has exceeded 2500 tons since 2017 and production continues to increase (though very little). There are many hydrographically suitable areas in the study area. However, in general, it is seen that the number of enterprises is very low despite the diversity of these hydrographic sources. When analyzed by districts, it is seen that the most facilities are in Çatak with 15 facilities. Gürpınar district is followed by 12 facilities. Aquaculture in the province of Van is at a level to meet the fish need of the entire region when its full potential is used. As of 2019, aquaculture capacity in the study area is 3779 tons. However, production remained at 2678 tons. This means that only 68% of the current capacity of aquaculture is used throughout the province. In the remaining 32%, there is no production. As a result, despite the high potential of aquaculture, Van province could not make the necessary progress. If the aquaculture potential in the province evaluates at a reasonable level, it will make significant contributions to the economy of the Eastern Anatolia and Southeastern Anatolia regions, in particular to Van in general.